FAKTOR YANG MEMPENGARUHI KEJADIAN ISPA PADA BALITA DI WILAYAH KERJA YANG BERKUNJUNG DI PUSKESMAS BATUA MAKASSAR - Ramli, Rachmat (Pusat riset dan Inovasi Nasional, 2022)
Acute Respiratory Infections (ARI) are upper and lower respiratory infections caused by infection or bacteria. According to WHO (2018), 40%-60% of the world's under-five population experience ARI. ARI occurs due to many factors, including LBW, Nutritional Status, Immunization Status, and Residential Density. This study aimed to determine whether there was a relationship between these factors and the incidence of ARI at the Batua Makassar Health Center. The design of this study used an analytical survey with a cross-sectional design. The research sample consisted of 90 children under five with a simple random sampling technique, and the measuring instruments used were questionnaires and KMS. Data analysis using chi-square test. The results of the study using the chi-square test obtained a value of P = 0.049 (LBW), P = 0.013 (nutritional status), P = 0.000 (research status), P = 0.001 (density of residence) because the -value = <0.05 then Ha is accepted, it means that there is a relationship of several factors to the incidence of ARI in toddlers at the Batua Makassar Health Center. From the results of this study, it can be said that the condition of LBW, nutritional status, immunization status, and density of residence has a significant relationship. Families are expected to add information by actively participating in activities carried out by health workers on reducing factors that can cause ARI in toddlers.